MAMLAKATIMIZDA MEHMONXONA BIZNESINING RIVOJLANISH TENDENSIYALARI - Reymbayeva Shaxnoza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the article is presented results of the hotel business in Uzbekistan analysis, the development trends, as well existing shortcomings in this field and their solutions. The statistical data for the average occupancy of all categories of hotels in Uzbekistan was presented for the of March 2022. In addition, the number of hotels in our Republic and the dissemination of hotels in regions were analyzed.